“Optimación de la línea de producción de la empresa lácteos Serranito del cantón Mejía" - Paredes Loayza, Mirella Jazmín (2021)
This research project was carried out in the company called Lácteos Serranito, which is located in the province of Pichicha, Mejía canton, Tambillo parish, with the aim of "OPTIMIZING AND IMPROVING THE COMPANY'S PRODUCTION LINE", Through field visits, personal interviews with both the General Manager and the administrative staff of the company, observations were found as shortcomings in some of the internal production processes of the company, which are disclosed in a more detailed and specific way in this present study. technical. In order to overcome all these inconsistencies, improvement models were proposed which basically used research techniques and methodologies such as takt time and the Deming cycle to determine exactly and in detail which are the parameters on which the company should focus. so that there is better performance in each of the production processes that the company contains. This improvement proposal was made with the purpose of increasing the client portfolio, positioning the brand in better competitive markets, generation and innovation of top quality products suitable for human consumption, reduction of costs in production times, hand of qualified work, increase of sources of employment and natural heritage of the company. The same that will increase gradually according to the production standards that the company needs to generate because this is directly related to the demand of customers and / or consumers. In addition, an economic evaluation was carried out, based on the need for the daily production increase that the company has to achieve this objective and demonstrate that the decision taken is economically viable and profitable in all its application phases. Keywords: Optimize, Production, Improvement, Design.